Precalculus (6th Edition) Blitzer

Published by Pearson
ISBN 10: 0-13446-914-3
ISBN 13: 978-0-13446-914-0

Chapter P - Section P.4 - Polynomials - Exercise Set - Page 56: 83



Work Step by Step

$(3x + 4y)^2 - (3x - 4y)^2$ $=(3x + 4y)(3x + 4y)-(3x - 4y)(3x - 4y)$ $=(9x^2+12xy+12xy+16y^2)-(9x^2-12xy-12xy+16y^2)$ $=(9x^2+24xy+16y^2)-(9x^2-24xy+16y^2)$ $=9x^2+24xy+16y^2-9x^2+24xy-16y^2$ $=48xy$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.